TOURISM OF BAKA RATU AS BIBAKKAH IN QURAN 3.96 WITH HAHSLM 472319 AND CONSTANT 12 - Aziz, Roikhan Mochamad (The journal of contemporary issues in business and government, 2021)
Purpose: the purpose of this study is to analyze tourism in the Ratu Baka area which is written as Bibakkah in the Quran 3.96. Methodology: This study uses descriptive analysis. The method used is the Hahslm 472319 with Holy Book. The object of this research is Ratu Baka, Quran 3.96 and 72 stupas. Results: The results are the Ratu Baka tourist complex and Borobudur is one area. By the word, Bibakkah means by bakkah in Quran 3.96 which refers to Ratu Baka. The builder of the 72 stupas is Ratu Baka reinforced by the word “placed” meaning it can be moved. The reflexivity of 3.96 is in the stupa in the form of 3 floors, 7+2 stupa which is 9, and factorization 16, 24, 32 in the form of 1+2+3, and 6+4+2 which is 6. Discussion: Tourism management in the Ratu Baka area is in the form of an empty building that has been relocated to Borobudur. Ratu Baka and Borobudur are under the same management company. The limit on the number of 72 stupas built holds phenomenal and absolute meanings. The largest historic temple building in the world, namely Borobudur has The 72 stupas refer to phenomenal occurrences with absolute and differential. Tourism management also needs to be done with a phenomenal modern physics pattern with quantum reality in its wave interference. The similarity is found in the meaning of 7 waves and 2 gaps in the interference physics process, then reflected in the code of the 72 stupas that were built. The research concludes that tourism management needs to develop the Ratu Baka area according to the Quran 3.96 in the form of the word Bibakkah with the constant Hahslm 472319 in the Covid economic era.